2021
DOI: 10.1038/s41438-021-00683-z
|View full text |Cite|
|
Sign up to set email alerts
|

The Cymbidium genome reveals the evolution of unique morphological traits

Abstract: The marvelously diverse Orchidaceae constitutes the largest family of angiosperms. The genus Cymbidium in Orchidaceae is well known for its unique vegetation, floral morphology, and flower scent traits. Here, a chromosome-scale assembly of the genome of Cymbidium ensifolium (Jianlan) is presented. Comparative genomic analysis showed that C. ensifolium has experienced two whole-genome duplication (WGD) events, the most recent of which was shared by all orchids, while the older event was the τ event shared by mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 71 publications
3
32
0
Order By: Relevance
“…The divergence time between the most closely related orchid plants B. striata and G. elata was estimated to be 55.1 Mya. Bletilla striata has experienced two WGD events, and the recent WGD was similar to that found in other orchid genomes (Ai et al., 2021; Chung et al., 2021; Niu et al., 2021; Yang, Gao, et al., 2021b; Zhang et al., 2017; Zhang et al., 2021), suggesting that this WGD was shared by all extant orchid genomes. There is sufficient evidence to confirm that WGD events have been frequent in the evolutionary history of flowering plant genomes, and they usually shape the evolutionary trajectory of genes and genomes, especially the genes related to plant‐specialized phenotypes and/or agronomic traits(Clark & Donoghue, 2017; Guo et al., 2013; Soltis & Soltis, 2016).…”
Section: Discussionsupporting
confidence: 64%
“…The divergence time between the most closely related orchid plants B. striata and G. elata was estimated to be 55.1 Mya. Bletilla striata has experienced two WGD events, and the recent WGD was similar to that found in other orchid genomes (Ai et al., 2021; Chung et al., 2021; Niu et al., 2021; Yang, Gao, et al., 2021b; Zhang et al., 2017; Zhang et al., 2021), suggesting that this WGD was shared by all extant orchid genomes. There is sufficient evidence to confirm that WGD events have been frequent in the evolutionary history of flowering plant genomes, and they usually shape the evolutionary trajectory of genes and genomes, especially the genes related to plant‐specialized phenotypes and/or agronomic traits(Clark & Donoghue, 2017; Guo et al., 2013; Soltis & Soltis, 2016).…”
Section: Discussionsupporting
confidence: 64%
“…Gene duplication plays an important role in plant evolution and is a main mechanism of gene family expansion. Three whole-genome duplication (WGD) events have occurred in A. thaliana [32], and C. ensifolium has experienced two WGD events [33]. The result showed that segmental and tandem duplication events occured unevenly on chromosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Given the conserved nature of gene structure within the same clade, we found that orchid KNOXs have a similar exon–intron structure compared to A. thaliana and O. sativa , except that most orchids exhibited longer intron length ( Figure 3C ). Long intron has been reported in almost all sequenced orchid species ( Cai et al, 2014 ; Zhang et al, 2016 , 2017 ; Yuan et al, 2018 ; Ai et al, 2021 ), which might be a unique feature of Orchidaceae. Longer introns are favored in the course of gene evolution because they promote the efficiency of natural selection by increasing the recombination between two adjacent exons ( Jo and Choi, 2015 ), which may account for the marvelous richness of orchids.…”
Section: Discussionmentioning
confidence: 98%